Correlation Between 25-Hydroxy-Vitamin D [25(Oh) D] Levels And Polycystic Ovary Syndrome In Obese Women: A Case-Control Study - Patabang, Jimmy; Madya, Fatmawati; Wewengkang, Ellen; Hamid, Firdaus; Abdullah, Nusratuddin; Chalid, Maisuri T (Journal of Neonatal Surgery, 2025)
Background: Polycystic ovary syndrome (PCOS) occurs around 38-88% in overweight or obese women. Obese women with PCOS tend to have lower serum vitamin D levels compared to lean women with PCOS. Objective: This study aimed to analyze the relationship between 25-hydroxy-vitamin D [25(OH)D] levels in obese women with PCOS. Methods: This case-control study was conducted on 80 obese women aged between 26-35 yrs old from January to December 2024 at Hasanuddin University hospital and Wahidin Sudirohusodo hospital, Makassar, Indonesia. All participants were divided into 2 groups: women with PCOS (n=40) and women without PCOS (n=40). All women were measured for body mass index (BMI) and Serum 25(OH)D levels were measured using enzyme-linked immunosorbent assay ELISA. Results: This study found that obese women with PCOS had 25(OH)D levels that were significantly lower than obese women without PCOS (p value=0.004). However, women with PCOS tend to have a higher BMI than women without PCOS (p value=0.052). Low 25(OH)D levels are weak correlation with increased BMI (r=-0.265, p value=0.017). Conclusion: Vitamin D levels were low in obese women with PCOS, therefore vitamin D supplementation in PCOS may be recommended.